Five secrets in a box - Brighton, Catherine (New York Dutton, 1987)
While Galileo sleeps, his young daughter Virginia, later known as Maria Celeste, explores his study and discovers some of the tools he uses in his scientific experiments.
Keywords: Galilei, Maria Celeste -- 1600-1634 -- Juvenile fiction; Galilei, Maria Celeste -- 1600-1634 -- Fiction; Galileo -- 1564-1642 -- Fiction; Fathers and daughters -- Fiction; Astronomers -- Fiction